Energy efficient and privacy protection window system for smart home using polymer-dispersed liquid crystals glass - Adam Reda Hasan Alhawari; Abdulkarem Hussien Almawgani; Hisham Alghamidi; Ayman Taher Hindi; Azzan Alyami; Abdulrahman Alyami; Yahya Aldaweis; Mahdi Algannas; Abdultawab Qahtan (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Hot climates smart home system is steadily advancing recently. The main concern is energy efficiency particularly in the Arabian Gulf region. Privacy is another prioritized concern culturally. This project presents a solution for both demanded priorities implementing a polymer-dispersed liquid crystals (PDLC) glass system. The proposed design was validated via a developed prototype that was measured experimentally. Its experimental results show about 39% improvement in energy saving compared to conventional systems without depriving the indoor-outdoor connections and the privacy of the smart home inhabitants. Furthermore, it also achieves several other additional goals, for instance, decreasing cost as well as wasted energy by automatically off the lighting and air conditioning systems whenever they are not in used. Moreover, it is also capable to significantly reduce the risk of harmful exposure to ultraviolet A/B (UVA/B) of solar radiations, which conventional curtains are not capable to protect.